The comparison of cyclopentolate and atropine in patients with refractive accommodative esotropia by means of retinoscopy, autorefractometry and biometric lens thickness - Çelebi, S; Aykan, Ü (Scriptor Publisher, 1999)
Purpose: In this study, we aimed to compare the cycloplegic effect of cyclopentolate HCI 1% and atropine sulphate 1% in patients with refractive accommodative esotropia by means of retinoscopy, autorefractometer and the measurement of lens thickness by biometry. Methods: Thirty-two patients with refractive accommodative esotropia aged from 5 to 10 (mean 6.8+/-1.4), had a deviation under 10 prism diopters, and underwent retinoscopic, autorefractometric and biometric study in dry and wet conditions. Results: The retinoscopic, autorefractometric and biometric findings of the right eye were 5.10+/-1.21 diopter (D), 5.03+/-1.20 D, 3.43+/-0.16 mm with cyclopentolate, and 5.2+/-1.2 D, 5.2+/-1.2 D, 3.4+/-0.1 mm with atropine. In the left eye, the measurements were 5.2+/-1.4 D, 5.1+/-1.4 D, 3.5+/-0.2 mm with cyclopentolate, and 5.3+/-1.2 D, 5.20+/-1.3 D, 3.4+/-0.2 mm with atropine, respectively. When these obtained data were compared by the Student's t test no statistical significance was found (p>0.05). Conclusions: We suggest that the cyclopentolate cycloplegia applied to the patients with refractive accommodative esotropia is sufficient to produce good cycloplegia, with an effect similar to atropine.
Keywords: refractive accommodative esotropia; cycloplegia; cyclopentolate; atropine; retinoscopy; autorefractometer; biometry; lens thickness